Hymenagaricus siamensis (Agaricaceae, Agaricales), a novel macrofungus from northern Thailand - Kumla, Jaturong; Suwannarach, Nakarin; Khuna, Surapong; Phonrob, Wiphawanee; Lumyong, Saisamorn (Phytotaxa, 2023)
A new macro-fungal species, described herein as Hymenagaricus siamensis, was collected from northern Thailand during the period from 2020 to 2022. This species is characterized by its small-sized basidiomata, a squamulose pileipellis consisting of pseudoparenchymatous tissue, yellowish-brown basidiospores and an absence of pleurocystidia and clamp connections. However, it is clearly distinguishable from H. nigroviolaceus by the presence of larger basidiospores and smaller pseudoparenchymatous cells in the squamulose pileus. Phylogenetic analysis of internal transcribed spacers (ITS) and large subunit (nrLSU) of the nuclear ribosomal DNA (rDNA) also revealed that the position of H. siamensis is well-supported within the genus Hymenagaricus, but distinct from other sequenced species. A full description, color photographs, illustrations and a phylogenetic tree showing the position of H. siamensis are provided. Comparisons between morphologically similar and related species have also been made and are discussed.